2013
DOI: 10.2215/cjn.10171012
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Nephrologist Visits to Patients on Hemodialysis across Dialysis Facilities and Geographic Locations

Abstract: SummaryBackground and objectives Geographic and other variations in medical practices lead to differences in medical costs, often without a clear link to health outcomes. This work examined variation in the frequency of physician visits to patients receiving hemodialysis to measure the relative importance of provider practice patterns (including those patterns linked to geographic region) and patient health in determining visit frequency.Design, setting, participants, & measurements This work analyzed a nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 18 publications
(13 reference statements)
1
42
0
Order By: Relevance
“…A recent study of variation in visit frequency found that patients who were recently hospitalized were 2% less likely to be seen four or more times than patients without a recent hospitalization. 14 This inverse association highlights an area where health care delivery can be improved. Section 3025 of the United States Affordable Care Act created a new pay-for-performance program wherein the CMS reduces Medicare payments to hospitals with excess standardized hospital readmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of variation in visit frequency found that patients who were recently hospitalized were 2% less likely to be seen four or more times than patients without a recent hospitalization. 14 This inverse association highlights an area where health care delivery can be improved. Section 3025 of the United States Affordable Care Act created a new pay-for-performance program wherein the CMS reduces Medicare payments to hospitals with excess standardized hospital readmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…26 Despite this, a recent study of variation in visit frequency found that patients who were recently hospitalized were 2% less likely to be seen four or more times than patients without a recent hospitalization. 27 Moreover, the depth of interaction may also be important, as demonstrated by data from the Dialysis Outcomes and Practice Patterns Study, which found that patients experienced improved survival when their providers spent more time conducting face-to-face visits at the outpatient hemodialysis unit. 28 Fourth, given the time constraints of dialysis, patients may be using the emergency department as a surrogate for their primary care provider.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, local provider practice patterns and economic incentives faced by individual providers explain a higher fraction of the variation in visit frequency. 19 Current reimbursement encourages visits to all patients, irrespective of their health needs. Policies that encourage more frequent visits to patients who actually benefit from additional visits, such as patients who recently started dialysis or who were recently discharged from the hospital, could lead to improvements in health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical basis for our choice of instrument comes from previous findings that provider visit frequency in hemodialysis is determined to a greater degree by dialysis facility location than individual patient characteristics, in addition to similarities among physician networks and observations that providers working in close proximity to one another share practice patterns. 19,[34][35][36][37] Using a two-stage least-squareslinear probability model,we measured the association between predicted visits in the first 90 days of dialysis and each outcome of interest. We controlled for patient demographic, socioeconomic, and comorbidity characteristics listed in Table 2.…”
Section: Instrumental Variable Analysesmentioning
confidence: 99%
See 1 more Smart Citation